Josh and the big wall! - Vischer, Phil.; Olsen, Chris; Nawrocki, Michael; Big Idea Productions ([Chicago] : Big Idea : Distributed by WEA, 2002)
After 40 years of wandering in the desert, the children of Israel finally get to go to the Promised Land! One little thing they've overlooked though ... Jericho, a city surrounded by huge walls. No one gets to the Promised Land without going through Jericho first!
Title from disc surface.
Based on the characters created by Phil Vischer and Mike Nawrocki.
Special features include: "The song of the Cebu!"; trailers; audio commentary; behind the scenes features; art gallery; Veggie karaoke; DVD-ROM content; Web site links; "Easter egg" hidden features.
Not rated.
DVD; Dolby digital 5.1 surround sound.
Keywords: Obedience -- Juvenile drama; Christian life -- Juvenile drama; Bible stories; Video recordings for the hearing impaired; Animated films; Children's films